GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 676 species occurrences available in GBIF matching the query: TaxonKey: Didelphis marsupialis Linnaeus, 1758 Country: Mexico. The dataset includes 676 records from 48 constituent datasets: 49 records from KUBI Mammalogy Collection. 5 records from CUMV Mammal Collection (Arctos). 6 records from The mammals collection (ZM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 12 records from Field Museum of Natural History (Zoology) Mammal Collection. 5 records from Museum of Comparative Zoology, Harvard University. 10 records from iNaturalist Research-grade Observations. 6 records from Mammals housed at MHNG, Geneva. 28 records from NMNH occurrence DwC-A. 13 records from CAS Mammalogy (MAM). 2 records from UMMZ Mammal Collection. 10 records from UMZC Zoological Specimens. 14 records from Colección de Mamíferos de la Sierra Volcánica Transversal de México (UAM-I). 47 records from Computarización de la Colección Nacional de mamíferos del Instituto de Biología, UNAM. 3 records from Distribución geográfica de las aves y los mamíferos de las zonas montanas de los estados de San Luis Potosí e Hidalgo circundantes de la Sierra Gorda. 6 records from Computarización de las colecciones de vertebrados terrestres de la Escuela Nacional de Ciencias Biológicas, IPN Fase 1: Estado de México, Hidalgo, San Luis Potosí y Tlaxcala. 3 records from Diversidad de los mamíferos de la Reserva de la biósfera Tehuacán-Cuicatlán, Puebla-Oaxaca, México. 14 records from Patrones de diversidad florística y faunística del área focal Ixcan, selva Lacandona, Chiapas. Mamíferos. 21 records from Computarización de las colecciones de vertebrados terrestres de la Escuela Nacional de Ciencias Biológicas, IPN - Fases 3. 4 records from Anfibios, reptiles y mamíferos del corredor biológico del norte de Yucatán depositados en las colecciones de la Escuela Nacional de Ciencias Biológicas. 13 records from Sistematización de las colecciones científicas del Instituto de Historia Natural y Ecología, (IHNE) Chiapas. 2 records from Computarización de las colecciones de vertebrados terrestres de la Escuela Nacional de Ciencias Biológicas, IPN - Fases 2. 15 records from Vertebrados terrestres del Corredor Biológico Sierra Madre del Sur, Chiapas, México. 8 records from Actualización de la base de datos de la colección mastozoológica de El Colegio de la Frontera Sur, San Cristóbal de las Casas. 2 records from Vertebrados terrestres del parque nacional Cañón del Sumidero, Chiapas, México. 107 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 3 records from Inventario de los mamíferos de las reservas de la biósfera Mapimí, La Michilía, El Cielo y Calakmul. 14 records from Mamíferos de los Parques Nacionales Lagunas de Montebello y Palenque, Chiapas. 1 records from Incorporación de nuevos registros de mamíferos de la región Sierra Norte de Oaxaca. 9 records from RBINS collections. 6 records from UWBM Mammalogy Collection. 47 records from LSUMZ Mammals Collection. 3 records from Paleobiology Database. 51 records from CNMA/Colección Nacional de mamíferos. 1 records from Vertebrate Zoology Division - Mammalogy, Yale Peabody Museum. 11 records from TTU Mammals Collection. 14 records from Colección de Mamíferos de la Sierra Volcánica Transversal de México (UAM-I). 10 records from Colección de Mamíferos del Museo de Zoología 'Alfonso L . Herrera', México (MZFC, UNAM). 1 records from UAZ Mammals. 13 records from CNMA/Colección de Mamíferos de la Estación de Biología Los Tuxtlas. 14 records from AMNH Mammal Collections. 6 records from Mammal Specimens. 1 records from Queensland Museum provider for OZCAM. 11 records from Geographically tagged INSDC sequences. 1 records from MSB Mammal Collection (Arctos). 13 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 20 records from Mammalogy Collection - Royal Ontario Museum. 1 records from Palaeobiology - Vertebrate Comparative Osteology Collection - Royal Ontario Museum. 20 records from Angelo State Natural History Collections (ASNHC) - Mammalogy Collection.
Keywords: GBIF; biodiversity; species occurrences